Modern Imaging of Myocarditis: Possibilities and Challenges - Baeßler, B.; Schmidt, M.; Lücke, C.; Blazek, S.; Ou, P.; Maintz, D.; Bunck, A. C. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Myocarditis is known as the chameleon of cardiac diseases. The symptoms and the course of disease vary greatly so that it is often challenging to establish a diagnosis. Early and accurate diagnosis is of utmost importance, since myocarditis is one of the leading causes of sudden cardiac death in young adults and represents an important precursor to dilated cardiomyopathy. Due to the constraints of the routinely used diagnostic approach, including clinical history and examination, laboratory testing, and electrocardiogram, different imaging modalities have emerged over the last decades as contributors to the noninvasive diagnosis of myocarditis. With this interdisciplinary review we would like to present the current state-of-the-art imaging of myocarditis across all available imaging modalities (i. e., echocardiography, cardiac magnetic resonance, cardiac computed tomography, and nuclear medicine). Furthermore, we present novel imaging techniques that might become useful in the near future for easier and more accurate diagnosis of this highly relevant disease.Key Points:• Different imaging modalities are increasingly used in the diagnostic workup of myocarditis.• Several emerging imaging techniques are currently on the way to becoming part of the clinical routine.• This review summarizes the diagnostic value of echocardiography, CMR, CT, and nuclear medicine imaging.• There is special focus on the possibilities and challenges of novel imaging tools within the different modalities.Citation Format:• Baeßler B, Schmidt M, Lücke C et al. Modern Imaging of Myocarditis: Possibilities and Challenges. Fortschr Röntgenstr 2016; 188: 915 – 925
Keywords: cardiac; inflammation; MR imaging; myocarditis; cardiac MRI